Criminal Law System in Indonesia and Its Comparison with Other Legal Systems - Amrizal Siagian; Nur Rohim Yunus; Fitriyani Zein (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
Criminal law in a general sense has the same aims and objectives in all systems universally. However, in its application, there are differences in methods and methods apart from being bound by standard rules which are the main basis as the basic norms of a country. The research method used in this study is a qualitative research method with a comparative studies approach. The results of the study state that there are similarities in the objectives of the criminal law system in several countries. However, in Indonesia, the legal system is based on the values of Pancasila and the 1945 Constitution and aspires to justice for all its people. The legal system in Indonesia recognizes the existence of legal pluralism, Islamic law, and customary law. This is not found in the legal system of other countries.Keywords: Legal System; Ratio; Criminal law Abstract:Hukum Pidana dalam pengertian umum memiliki kesamaan maksud dan tujuan pada semua sistem secara universal. Namum dalam aplikasinya, terdapat perbedaan cara dan metode selain terikat pada aturan baku yang menjadi landasan utama sebagai norma dasar suatu negara. Metode penelitian yang digunakan pada penelitian ini adalah metode penelitian kualitatif dengan pendekatan comparative studies. Hasil penelitian menyatakan bahwa ada kesamaan tujuan pada sistem hukum pidana pada beberapa negara. Namun pada negara Indonesia, sistem hukumnya berdasarkan nilai-nilai Pancasila dan UUD 1945 serta mencita-citakan keadilan bagi seluruh rakyatnya. Sistem hukum di Indonesia mengakui adanya pluralisme hukum, hukum Islam, dan hukum adat. Hal inilah yang tidak terdapat pada sistem hukum negara lain.Kata Kunci: Sistem Hukum; Perbandingan; Hukum Pidana